Business Model Canvas : Hyper Grabber / Mohamed Zuheel Zaid - Zaid, Mohamed Zuheel (2020)
To create hyper grabber metal and polymer is required. Hyper grabber required high quality polymer and high quality metal for its toughness and long lasting of this product. Electronic device is the key resources for hyper grabber for the switch and its adjustable shaft.